Perdagangan Perempuan: Perspektif HAM dan Filsafat Hukum Islam - Fuad Mustafid (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2016)
Trafficking in women or also popular as women trafficking is a crime that has lasted quite a long time and in many countries in this world, not least in Indonesia. Efforts are being made by the government of this country to overcome or eliminate the practice of trafficking in women, but the results are not / not satisfactory. The women in this country continue to be victims of trafficking practices in humane. Religious and legal provisions exist in this country as well as powerless against the phenomena of women trade practices. This paper examines the phenomenon of trafficking in women (women trafficking) from a human rights perspective and philosophy of Islamic law. Thus, this paper was practically a comparative study, in which the issue of trafficking of women examined from two perspectives at once, which is a human rights perspective and philosophy of Islamic law. From this study, we concluded that the practice of trafficking in women is part of the crimes against humanity that are not only contrary to human rights, but also contrary to the provisions of the religious (Islamic law).